The Complete Genome and Physiological Analysis of the Eurythermal Firmicute Exiguobacterium chiriqhucha Strain RW2 Isolated From a Freshwater Microbialite, Widely Adaptable to Broad Thermal, pH, and Salinity Ranges - White, Richard Allen; Soles, Sarah A.; Gavelis, Greg; Gosselin, Emma; Slater, Greg F.; Lim, Darlene S. S.; Leander, Brian; Suttle, Curtis A. (Frontiers in Microbiology, 2019)
Members of the genus Exiguobacterium are found in diverse environments from marine, freshwaters, permafrost to hot springs. Exiguobacterium can grow in a wide range of temperature, pH, salinity, and heavy-metal concentrations. We characterized Exiguobacterium chiriqhucha strain RW2 isolated from a permanently cold freshwater microbialite in Pavilion Lake, British Columbia using metabolic assays, genomics, comparative genomics, phylogenetics, and fatty acid composition. Strain RW2 has the most extensive growth range for temperature (4 to 50 ˚C) and pH (5 to 11) of known Exiguobacterium isolates. Strain RW2 genome predicts pathways for wide differential thermal, cold and osmotic stress using cold and heat shock cascades (e.g., csp and dnaK), choline and betaine uptake/biosynthesis (e.g., opu and proU), antiporters (e.g., arcD and nhaC Na+/K+), membrane fatty acid unsaturation and saturation. Here we provide the first complete genome from Exiguobacterium chiriqhucha strain RW2, which was isolated from a freshwater microbialite. Its genome consists of a single 3,019,018 bp circular chromosome encoding over 3,000 predicted proteins, with a GC% content of 52.1%, and no plasmids. In addition to growing at a wide range of temperatures and salinities, our findings indicate that RW2 is resistant to sulfisoxazole and has the genomic potential for detoxification of heavy metals (via mercuric reductases, arsenic resistance pumps, chromate transporters, and cadmium-cobalt-zinc resistance genes), which may contribute to the metabolic potential of Pavilion Lake microbialites. Strain RW2 could also contribute to microbialite formation, as it is a robust biofilm former and encodes genes involved in the deamination of amino acids to ammonia (i.e., L-asparaginase/urease), which could potentially boost carbonate precipitation by lowering the local pH and increasing alkalinity. We also used comparative genomic analysis to predict the pathway for orange pigmentation that is conserved across the entire Exiguobacterium genus, specifically, a C30 carotenoid biosynthesis pathway is predicted to yield diaponeurosporene-4-oic acid as its final product. Carotenoids have been found to protect against ultraviolet radiation by quenching reactive oxygen, releasing excessive light energy, radical scavenging, and sunscreening. Together these results provide further insight into the potential of Exiguobacterium to exploit a wide range of environmental conditions, its potential roles in microbialites/microbial mats.